Frequency of Osteomalacia and Vitamin D Deficiency in Elderly Patient Presenting at a Tertiary Care Hospital - Jamal Ahmad Khan, Bakht Babar, Azmat Ali Khan, Sana, Zakirullah Khan, (Pakistan Journal of Medical & Health Sciences, 2024)
Introduction: Vitamin D deficiency leads to the bone hypomineralization condition known as osteomalacia in peoples and is linked to other non-skeletal diseases. Objectives: To determine the frequency of osteomalacia and vitamin d deficiency in elderly patient presenting at a tertiary care hospital. Study Design: Cross sectional study Settings: Department of Diabetes and endocrinology Hayatabad medical complex Peshawar Materials & Methods: Total 140 patients aged 50 years and above presenting with body pain and weakness who required medical treatment at hospital for various health concerns. Patients with known metabolic bone disorders other than osteomalacia, patients receiving vitamin D supplementation or specific treatments for bone disorders were excluded. Participants underwent a thorough clinical assessment, including medical history review, physical examination, and assessment of musculoskeletal symptoms associated with osteomalacia. Blood samples were collected to measure serum levels of 25-hydroxyvitamin D [25(OH)D], the biomarker for vitamin D status. Additional biochemical markers, such as alkaline phosphatase and parathyroid hormone levels, were also assessed to aid in the diagnosis of osteomalacia. Collected data of study variables were analyzed using statistical software (SPSS version 25). Results: Regarding gender, a total of 60 patients were male, constituting 42.85% of the population, while 80 patients were female, representing 57.14%. Musculoskeletal pain was reported in 80 individuals, representing 57.1% of the population. Proximal muscle weakness was observed in 50 patients, accounting for 35.7%. Additionally, 40 patients (28.6%) had a history of fractures. Vitamin D deficiency was identified in 68(48.57%), while osteomalacia was in 11(7.85%) patients. Practical Implication: Understanding the interplay between thyroid disorders and bone health can guide more comprehensive management strategies in this vulnerable population at tertiary care hospitals. Conclusion: In conclusion, our study reveals a relatively high prevalence of biochemical osteomalacia 7.85% among Pakistani old age patients challenging previous estimates in other populations Keywords: Association, Bone Hypomineralization, Non-skeletal Disorders, Osteomalacia, Vitamin D Deficienc